Pemberdayaan UMKM melalui Inovasi Marketing berbasis Teknologi Informasi: Empowering MSMEs through Information Techology-based Marketing Innovation - Rela Adi Himarosa; Krisdiyanto Krisdiyanto; Primadian Adhi Wardana; Nur Rachman Maulana; Fajar Sofyantoro (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Pondok Pesantren Asy-Syifa' Muhammadiyah (PPAM) in Yogyakarta established several Micro, Small and Medium Enterprises (MSMEs) including production units of tempeh, mineral water, coffee, and donut. The main obstacle experienced by the MSMEs is the traditional marketing system which limits the sales of products. The current program aimed to assist the adoption of information technology, especially in marketing techniques using social media and e-commerce. The activities included discussions with MSMEs owners, socialization of marketing techniques, creating social media accounts, making of product catalogs, and evaluation. In general, all the activities could be carried out as targeted. After participating in this program, the MSME owners at PPAM are able to use social media and e-commerce to increase product marketing and sales.